Pengaruh Pembelajaran Pengantar Bisnis, Kewirausahaan, Studi Kelayakan Bisnis Terhadap Minat Mahasiswa Menjadi Pengusaha Mandiri - Syafril, Syafril; Yemima, Yemima; Kessi, Andi Makkulawu Panyiwi; Fahmi, Muhammad; Fadilah, Neti Rosiana (Universitas Respati Indonesia, 2024)
This research aims to determine and test students' interest in entrepreneurship after learning about Introduction to Business, Entrepreneurship and Business Feasibility Studies at college. Data were collected using a questionnaire using Google Form which was distributed via the WhatsUp Group belonging to the research lecturer and used a descriptive quantitative approach with multiple linear regression methods, T Test and F Test (SPSS). The population was taken from a number of WhatUp Groups owned by research lecturers from students from various universities. The sample obtained was 122 students from universities in Banjarmasin and Timika Papua. The research results show that learning Introduction to Business and Business Feasibility Studies partially has a significant and positive effect on students' interest in becoming independent entrepreneurs, while the Entrepreneurship variable has no significant effect. Simultaneous test results show that the variables Introduction to Business, Entrepreneurship and Business Feasibility Study have a significant and positive effect on students' interest in becoming independent entrepreneurs. The results of this research can be used as a reference for further research and government policy making in the fields of education and entrepreneurship.